Effectiveness of Interdisciplinary Teaching Approach on Cognitive Structure About Proteins - Acarlı, Dilek Sultan (SCAD Independent, 2023)
In this study, the effect of teaching the subject of proteins with an interdisciplinary approach on students' cognitive structures was investigated. For this purpose, it was examined whether a course taught with an interdisciplinary approach effectively develops different perspectives and establishes relationships between concepts belonging to different disciplines. The study group in this research, which used a quasi-experimental design, was composed of 28 high school students (14 of whom were assigned to the experimental group and 14 to the control group). The subject of proteins was taught to the control group in a disciplinary approach while to the experimental group in an interdisciplinary approach. The effects of the approaches on students' cognitive structures were determined using a word association test. The answers obtained from the word association test were analyzed by qualitative content analysis. As a result of the analysis, models were created that show the change in the student's cognitive structures. As a result of the research, it was observed that the interdisciplinary approach increased the students' ability to think in the framework of different disciplines.